Preliminary Findings of a National Survey of Black ADRD Family Caregivers. (17th December 2021) - Robinson-Lane, Sheria; Johnson, Florence; Mazzara, Nicholas; DeMarco, Kayla; Dinov, Ivaylo
Abstract: The National Caregiver Survey aims to capture a representative sample of Black Alzheimer's disease and/or related dementias (ADRD) family caregivers who are 55+ to better understand the relationships between adaptation to caregiving, coping, and health. Following targeted social media marketing, ADRD family caregivers (n=60) completed an electronic survey capturing over 200 data elements. Analysis was completed using Spearman correlation coefficients. Preliminary results suggest that 55% of participants were hypertensive (n=33) and 27% (n=16) had diabetes. Participants were generally overweight with an average BMI of 29. 28% (n=17) of the sample were smokers. A negative correlation was identified between the level of care needs of the recipients (IADLs) and alcohol use (p=0.037). There was also a correlation between identifying positive aspects of caregiving and adaptive coping (p=0.045). Caregiver support programs should facilitate development of effective coping strategies for new family caregivers, with particular attention on smoking cessation, brain-healthy diet, and exercise.